Application of Data Mining in Classification Fresh Milk Production by Province Using K-Means Algorithm - Afifah Wulandari; M. Safii (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2023)
The need for fresh milk is currently experiencing a fairly rapid development as can be seen in terms of the domestic market, here researchers want to increase the productivity and quality of fresh milk production. The data to be used is data from the Central Bureau of Statistics. The method in this study is the K-means clustering algorithm which is grouped into 2 clustering, namely high and low. The results of this study are 1 high-level cluster province, 24 low-level cluster provinces